Augmenting Audience Actualization: Using Q-Methods Analysis to Determine Programming Priorities for One State’s Cooperative Extension System - Lauri M Baker; Caitlynne Youmans; Megan Cantrell; Quisto Settle; Cheng-Xian Yang; Jason Bolton; Hannah Carter (Journal of Applied Communications, 2025)
Cooperative Extension services play a valuable role in empowering communities through Extension programming. Extension must adapt to evolving societal needs by understanding and addressing its diverse audiences. Audience segmentation is a fundamental aspect of marketing efforts in Extension communication. Previous work has identified that Extension programs are “the best kept secret,” limited in marketing by its lack of a clear audience. This qualitative study pursued the differences in perceptions of Extension priority programming areas among a stakeholder audience of professionals and college students residing in [state]. Utilizing Q-Sort methodology to identify these stakeholder perspectives, factor analysis revealed the professionals highly value youth development, community-based programming, and environmental programming when related to community development. Students’ values toward programming, however, align with their academic interests. For example, students pursuing forestry highly value environmental programming efforts whereas students in business value human-focused developmental programming. Results in this study underscore the need for targeted communication efforts in state Extension priority programming based on audience segmentation to empower and serve diverse communities. Recommendations identified in this study highlight the necessity for state Extension systems to engage its actors in programming needs to enhance public value. This approach can serve as a model to Extension systems across the U.S. as a guide to understanding diverse audiences in an ever-changing society.
Keywords: Extension; Q-Sort; programming; audience segmentation; uses and gratifications theory